The effectiveness of reality group counseling in reducing communication anxiety among Islamic guidance and counselling students - Widyarto, Wikan Galuh; Rahmawati, Lutvia; Ramli, M (Fakultas Dakwah dan Komunikasi UIN Walisongo, 2024)
Purpose - The purpose of this study was to (1) determine the level of communication anxiety of students and (2) determine the degree of effectiveness of reality group counseling in reducing student communicative anxieties.Method - This research uses a quantitative type with a design quasy esxperiment. Purposive sampling is used as a sample-taking technique to look at the specific characteristics of the sample. The subject of the study is a student of Islamic Guidance and Counseling at Islamic State University Sayyid Ali Rahmatullah Tulungagung, who is indicated to have high communication anxiety. A total of 7 students are divided into two groups, namely the experimental group and the control group.Result - The results showed that the experimental group's Independent Test T-Test sample showed an average score of 131.75, and the control group showed 177.67. This study showed a decrease in student communication anxiety levels after treatment, which means that reality group counseling is quite effective in reducing student communication anxieties.Implication – From the research results, it is hoped that students will increase their insight and knowledge about communication anxiety, and students are expected to benefit from the reality group counseling that has been provided to reduce student communication anxiety.Originality/Value - This research is the first study that used the intervening variable of Reality Group Counseling to Reducing Anxiety by Communicating College Islamic Guidance and Counselling.***Tujuan - Tujuan dari penelitian ini adalah untuk (1) mengetahui tingkat kecemasan berkomunikasi siswa dan (2) mengetahui tingkat efektivitas konseling kelompok realitas dalam menurunkan kecemasan berkomunikasi siswa.Metode - Penelitian ini menggunakan jenis kuantitatif dengan desain quasy eksperiment. Purposive sampling digunakan sebagai teknik pengambilan sampel dengan melihat ciri-ciri khusus dari sampel. Subjek penelitian adalah mahasiswa Bimbingan dan Konseling Islam di Universitas Islam Negeri Sayyid Ali Rahmatullah Tulungagung yang terindikasi memiliki kecemasan komunikasi yang tinggi. Sebanyak 7 mahasiswa yang dibagi menjadi dua kelompok, yaitu kelompok eksperimen dan kelompok kontrol.Hasil - enelitian menunjukkan bahwa sampel Independent Test T-Test kelompok eksperimen menunjukkan skor rata-rata 131,75, dan kelompok kontrol menunjukkan 177,67. Penelitian ini menunjukkan adanya penurunan tingkat kecemasan komunikasi siswa setelah diberikan perlakuan, yang berarti konseling kelompok realitas cukup efektif dalam menurunkan kecemasan komunikasi siswa.Implikasi - Dari hasil penelitian diharapkan mahasiswa menambah wawasan dan pengetahuan mengenai kecemasan komunikasi, serta mahasiswa diharapkan dapat mengambil manfaat dari konseling kelompok realitas yang telah diberikan untuk menurunkan kecemasan komunikasi mahasiswa.Orisinalitas/Nilai - Penelitian ini merupakan penelitian pertama yang menggunakan variabel intervening Konseling Kelompok Realitas terhadap Penurunan Kecemasan Berkomunikasi Bimbingan dan Konseling Islam Perguruan Tinggi.